Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

Greenworld: Think Green for the Word. Learning Teaching Training Activities (LTTA). Workshop: Entrepreneurship, Green Business - Schneider, Jennifer Nicole

Greenworld: Think Green for the Word. Learning Teaching Training Activities (LTTA). Workshop: Creative Thinking - Schneider, Jennifer Nicole

Greenworld: Think Green for the Word. Learning Teaching Training Activities (LTTA). Workshop: Canvas Model - Schneider, Jennifer Nicole

EU-CERT. First Transnational Project Meeting. Presentation at the EU-CERT Meeting: Financial, Marketing and Dissemination. - Schneider, Jennifer Nicole

Family Business Library. Presentation at the LTTA of FBL: Motivation, Barriers and Problems while starting a business - Schneider, Jennifer Nicole

Nutzung von Process Mining in RPA-Projekten - Brock, Jonathan; von Enzberg, Sebastian; Kühn, Arno; Dumitrescu, Roman (Praxishandbuch Robotic Process Automation (RPA))

Adapting the product design to the circular economy using R-principles - Scholtysik, Michel; Rohde, Malte; Koldewey, Christian; Dumitrescu, Roman

Report on the E-TEMS 2022 Doctoral Workshop “Smart Cities as System of Systems” - Kaiser, Lydia; Kapp, Alexandra; Wardzinska, Katarzyna; Hegyi, Dora; Kobler, Corinna; Venegas, Jaime; Schrader, Elena; Tissen, Denis; Mundt, Enrik (2022 IEEE European Technology and Engineering Management Summit (E-TEMS))

Influence of Processing Glass-Fiber Filled Plastics on Different Twin-Screw Extruders and Varying Screw Designs on Fiber Length and Particle Distribution - Rüppel, Annette; Wolff, Susanne; Oldemeier, Jan Philipp; Schöppner, Volker; Heim, Hans-Peter (Polymers)
Due to their valuable properties (low weight, and good thermal and mechanical properties), glass fiber reinforced thermoplastics are becoming increasingly important. Fiber-reinforced thermoplastics are mainly manufactured by injection molding and extrusion, whereby the extrusion compounding process is primarily used to produce fiber-filled granulates. Reproducible production of high-quality components requires a granulate in which the fiber length is even and high. However, the extrusion process leads to the fact that fiber breakages can occur during processing. To enable a significant quality enhancement, experimentally validated modeling is required. In this study, short glass fiber reinforced thermoplastics (polypropylene) were produced on two different twin-screw extruders. Therefore, the machine-specific process behavior is of major interest regarding its influence. First, the fiber length change after processing was determined by experimental investigations and then simulated with the SIGMA simulation software. By comparing the simulation and experimental tests, important insights could be gained and the effects on fiber lengths could be determined in advance. The resulting fiber lengths and distributions were different, not only for different screw configurations (SC), but also for the same screw configurations on different twin-screw extruders. This may have been due to manufacturer-specific tolerances.
Keywords: Polymers and Plastics; General Chemistry

Identification of Human and Organizational Key Design Factors for Digital Maturity – A Fuzzy-Set Qualitative Comparative Analysis - Schneider, Martin; Hellweg, Talea Davina; Menzefricke, J. S. (Proceedings of the Design Society)
Abstract This paper examines how human and organizational factors need to be designed to achieve strong technological maturity of either the products or the production process. In a fuzzy-set qualitative comparative analysis (fs/QCA), a combination of intensive training and strong worker participation is found to be associated with strong technological maturity in the two organizational contexts: firms with a strong entrepreneurial culture and in large firms oriented towards customer-oriented innovation. Overall, the paper uncovers designs or causal recipes for a successful digital transformation.

Erst Überfluss, dann überflüssig? Erneuerungsdialoge zwischen Unternehmensgeschichte und (allgemeiner) Geschichtswissenschaft - Staffel, Florian Lukas

Co-creating business value through IT-business operational alignment in inter-organisational relationships: Empirical evidence from regional networks - Trang, S.; Mandrella, M.; Marrone, M.; Kolbe, L. (European Journal of Information Systems)

What to do after a data breach? Examining apology and compensation as response strategies for health service providers - Masuch, K.; Greve, M.; Trang, S. (Electronic Markets)

Apologize or Justify? Examining the Impact of Data Breach Response Actions on Stock Value of Affected Companies - Masuch, K.; Greve, M.; Trang, S. (Computers & Security)

Smart cities and smart governance models for future cities - Nastjuk, I.; Trang, S.; Papageorgiou, E. (Electronic Markets)

Künstliche Intelligenz in der industriellen Arbeitswelt - Papenkordt, Jörg; Gabriel, Stefan; Thommes, Kirsten; Dumitrescu, Roman
Im Rahmen dieser Studie wird der Status Quo des KI-Einsatzes in der industriellen Arbeitswelt in der Region OstWestfalenLippe erfasst und beschrieben. Dadurch wird eine Grundlage geschaffen, um eine zielführende Unterstützung der Gestaltung von durch Künstliche Intelligenz (KI) gestützter Arbeitsprozesse in Unternehmen zu ermöglichen, indem beispielsweise bedarfsbezogene Maßnahmen entwickelt und durchgeführt sowie weiterer Forschungsbedarf aufgezeigt wird. Die Befragung wurde im Jahr 2021 von dem Kompetenzzentrum Arbeitswelt.Plus sowie dem Spitzencluster it’s OWL initiiert. Dabei sind drei Zielgruppen – Unternehmensleitung, Personalabteilung (HR) sowie Arbeitnehmer*innen – adressiert worden. Insgesamt nahmen 317 Personen aus 89 verschiedenen Unternehmen bzw. Organisationen an der Befragung teil – zu 38 % Unternehmer*innen, zu 13 % Personaler*innen und zu 49 % Arbeitnehmer*innen. Die meisten der Teilnehmenden stammten aus der Elektroindustrie, dem Maschinenbau sowie dem Informations- und Kommunikationstechnologie (IKT)-Sektor. Die Befragungsergebnisse zeigen, dass sich die meisten Unternehmen in der Anfangsphase der KI-Nutzung befinden. Zwischen einzelnen Unternehmensbereichen und verschiedenen Branchen zeigen sich gewisse Unterschiede in der Nutzungsphase. Die Befragten stehen aktuell vor der Nutzung von vor allem teilautonomen KI-Systemen, die ausführende und analytische menschliche Tätigkeitenbeispielsweise durch Informationsbereitstellungen unterstützen. Wesentliche Ziele der KI-Nutzung sind die Effizienzsteigerung, Qualitätsverbesserung, Entscheidungsoptimierung sowie Unterstützung der Arbeitnehmer*innen. Allerdings werden in allen Unternehmen die fehlende Expertise sowie insgesamt die Komplexität des Themenfelds als Hinderungsgründe identifiziert. In allen Unternehmen und allen Unternehmensbereichen werden hohe Auswirkungen durch KI erwartet. Auf die Arbeitsgestaltung werden insgesamt eher positive Auswirkungen erwartet. Die Befragten schätzen die Bedeutung von KI, ihre Aufgeschlossenheit sowie ihr Vertrauen gegenüber KI als insgesamt hoch ein, ihr Verständnis von KI dagegen eher als gering. Tendenziell zeigt sich eine große Diskrepanz zwischen Selbst- und Fremdbild mit einer teils deutlich negativeren Wahrnehmung anderer. Die Befragten erwarten außerdem steigende Kompetenzanforderungen sowie einen hohen Weiterbildungsbedarf, insbesondere bezüglich des grundlegenden Verständnisses über KI. In den wenigsten Unternehmen existiert jedoch ein gezieltes Weiterbildungsangebot. Die Erkenntnisse aus der Befragung fließen im Rahmen des Kompetenzzentrums Arbeitswelt.Plus in die gezielte Gestaltung und Einführung KI-gestützter Arbeitsformen sowie bedarfsgerechter Unterstützungsangebote ein. Die hohe Komplexität der KI-Einführung sowie die sowohl technischen als auch mitarbeiterbezogenen Herausforderungen verdeutlichen den Bedarf für eine soziotechnische Perspektive und ein systematisches Vorgehen bei der Gestaltung dieses vielschichtigen Themenfelds.

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

Since Albert and Whetten: the dissemination of Albert and Whetten’s conceptualization of organizational identity - Knorr, Karin; Hein-Pensel, Franziska (Management Review Quarterly)
Abstract Since the seminal work of Albert and Whetten, the organizational identity concept has become ubiquitous and highly relevant in various fields. This study systematically reviews how Albert and Whetten’s concept of organizational identity has been disseminated in different research areas. It employs quantitative (topic modeling) and qualitative text analysis, as well as a network analysis to examine a sample of 1,041 papers published between 1985 and mid-2022 that cite Albert and Whetten’s seminal work. Using this method of systematic literature analysis, the current study investigates the criteria of the basic definition and hypotheses mentioned in their work that contribute to its increasing significance, and those with the potential to become substantial aspects of future organizational identity research. Accordingly, Albert and Whetten’s conceptualization of organizational identity is often partially adopted in the literature. Thus, this study contributes to organizational identity research by unveiling further research questions on the evolving character of organizational identity, research methodology, and quantitative operationalization, on the basis of Albert and Whetten’s organizational identity conceptualization.
Keywords: Strategy and Management; Business; Management and Accounting (miscellaneous)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia Amelie; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

When do individuals choose care robots over a human caregiver? Insights from a laboratory experiment on choices under uncertainty - Hoppe, Julia A.; Tuisku, Outi; Johansson-Pajala, Rose-Marie; Pekkarinen, Satu; Hennala, Lea; Gustafsson, Christine; Melkas, Helinä; Thommes, Kirsten (Computers in Human Behavior Reports)
Keywords: Artificial Intelligence; Cognitive Neuroscience; Computer Science Applications; Human-Computer Interaction; Applied Psychology; Neuroscience (miscellaneous)

Perception of Society’s Trust in Care Robots by Public Opinion Leaders - Hoppe, Julia Amelie; Melkas, Helinä; Pekkarinen, Satu; Tuisku, Outi; Hennala, Lea; Johansson-Pajala, Rose-Marie; Gustafsson, Christine; Thommes, Kirsten (International Journal of Human–Computer Interaction)
Keywords: Computer Science Applications; Human-Computer Interaction; Human Factors and Ergonomics

Organisation der dualen Berufsausbildung zum/zur Verkäufer:in und Kaufmann:frau im Einzelhandel im Zeichen der COVID-19-Pandemie. - Sommer, Christian; Szczesny, Daniela (Berufsausbildung zwischen Hygienemaßnahmen und Lockdown(s). Folgen für die schulische und außerschulische Berufsausbildung in Schule, im Betrieb und bei Bildungsträgern.)
One of the most powerful events in the still young 21st century is certainly the outbreak of the coronavirus and the following COVID-19 pandemic. Massive economic as well as social distress caused worldwide devastation. In Germany, not only stores, factories, cultural facilities were closed, but also – for the first time in history – schools were closed nationwide. Closed working sites and vocational schools, as well as working sites, which remained open due to their systemic relevance, led to so far unknown challenges in Germany’s vocational education system. A very good example are the dual apprenticeships, such as trained retail salesman, which were only partially affected by closures. The main goal of education policy was to compensate personal communication and interaction via digital media. This article’s main aim is to reveal the strategies vocational schools have developed to overcome the challenges they had to face because of the pandemic.
Keywords: COVID-19; Digitalization; Vocational education and training; Retail

Zum Ausmaß und Zusammenhang der unterrichtsbezogenen Nutzung digitaler Medien mit der Medienkompetenz von Lehrkräften unter Berücksichtigung von Hintergrundmerkmalen - Caruso, Carina; Drossel, Kerstin; Heldt, M (Lehrerbildung auf dem Prüfstand)

Motivate the Crowd or Crowd-Them Out? The Impact of Local Government Spending on the Voluntary Provision of a Green Public Good - Bartels, Lara; Kesternich, Martin
Keywords: General Earth and Planetary Sciences; General Environmental Science

More Money or Better Procedures? Evidence From an Energy Efficiency Assistance Program - Chlond, Bettina; Goeschl, Timo; Kesternich, Martin
Keywords: General Earth and Planetary Sciences; General Environmental Science

The Intention-Behavior Gap in Climate Change Adaptation - Kesternich, Martin; Osberghaus, Daniel; Botzen, Willem Jan Wouter
Keywords: General Earth and Planetary Sciences; General Environmental Science

Gas- statt Preisbremse: Wie die Umsetzung von Unterstützungsprogrammen zum Gassparen für Haushalte und Unternehmen gelingen kann - Kesternich, Martin; von Graevenitz, Kathrine

Pariser Klimaschutzabkommen – Berichtsstandards und Begleitanalysen nationaler Klimaschutzbeiträge stärken - Kesternich, Martin; Will, Ulrike; Manger-Nestler, Cornelia

Wie lässt sich die Energieeffizienz in einkommensschwachen Haushalten steigern? - Chlond, Bettina; Goeschl, Timo; Kesternich, Martin

Design and Evaluation of AR-Assisted End-User Robot Path Planning Strategies - Krings, Sarah Claudia; Yigitbas, Enes; Biermeier, Kai; Engels, Gregor (Proceedings of the 14th ACM SIGCHI Symposium on Engineering Interactive Computing Systems (EICS 2022))

Konzeptpapier zur Konferenz "Geschichte im digitalen Wandel? Geschichtskultur – Erinnerungspraktiken – Historisches Lernen"

Problematisches Sehen illusionärer Schönheit: die Armida-Episode in Torquato Tassos 'Gerusalemme liberata' - Steigerwald, Jörn (La Forme idéale à la Renaissance / Forma ideale durante il Rinascimento)

Post-rousseauistische Kulturanthropologie: Francois-René de Chateaubriands Erzählung "Atala" - Steigerwald, Jörn (Romanistische Zeitschrift für Literaturgeschichte)

Exploring the Feature Space of TSP Instances Using Quality Diversity - Bossek, Jakob; Neumann, Frank (Proceedings of the Genetic and Evolutionary Computation Conference)
Generating instances of different properties is key to algorithm selection methods that differentiate between the performance of different solvers for a given combinatorial optimization problem. A wide range of methods using evolutionary computation techniques has been introduced in recent years. With this paper, we contribute to this area of research by providing a new approach based on quality diversity (QD) that is able to explore the whole feature space. QD algorithms allow to create solutions of high quality within a given feature space by splitting it up into boxes and improving solution quality within each box. We use our QD approach for the generation of TSP instances to visualize and analyze the variety of instances differentiating various TSP solvers and compare it to instances generated by established approaches from the literature.
Keywords: instance features; instance generation; quality diversity; TSP

Evolutionary Diversity Optimization for Combinatorial Optimization: Tutorial at GECCO’22, Boston, USA - Bossek, Jakob; Neumann, Aneta; Neumann, Frank (Proceedings of the Genetic and Evolutionary Computation Conference Companion)

BBE: Basin-Based Evaluation of Multimodal Multi-objective Optimization Problems - Heins, Jonathan; Rook, Jeroen; Schäpermeier, Lennart; Kerschke, Pascal; Bossek, Jakob; Trautmann, Heike (Parallel Problem Solving from Nature (PPSN XVII))
In multimodal multi-objective optimization (MMMOO), the focus is not solely on convergence in objective space, but rather also on explicitly ensuring diversity in decision space. We illustrate why commonly used diversity measures are not entirely appropriate for this task and propose a sophisticated basin-based evaluation (BBE) method. Also, BBE variants are developed, capturing the anytime behavior of algorithms. The set of BBE measures is tested by means of an algorithm configuration study. We show that these new measures also transfer properties of the well-established hypervolume (HV) indicator to the domain of MMMOO, thus also accounting for objective space convergence. Moreover, we advance MMMOO research by providing insights into the multimodal performance of the considered algorithms. Specifically, algorithms exploiting local structures are shown to outperform classical evolutionary multi-objective optimizers regarding the BBE variants and respective trade-off with HV.
Keywords: Anytime behavior; Benchmarking; Continuous optimization; Multi-objective optimization; Multimodality; Performance metric

Co-Evolutionary Diversity Optimisation for the Traveling Thief Problem - Nikfarjam, Adel; Neumann, Aneta; Bossek, Jakob; Neumann, Frank (Parallel Problem Solving from Nature (PPSN XVII))
Recently different evolutionary computation approaches have been developed that generate sets of high quality diverse solutions for a given optimisation problem. Many studies have considered diversity 1) as a mean to explore niches in behavioural space (quality diversity) or 2) to increase the structural differences of solutions (evolutionary diversity optimisation). In this study, we introduce a co-evolutionary algorithm to simultaneously explore the two spaces for the multi-component traveling thief problem. The results show the capability of the co-evolutionary algorithm to achieve significantly higher diversity compared to the baseline evolutionary diversity algorithms from the literature.
Keywords: Co-evolutionary algorithms; Evolutionary diversity optimisation; Quality diversity; Traveling thief problem

Process-Oriented Stream Classification Pipeline: A Literature Review - Clever, Lena; Pohl, Janina Susanne; Bossek, Jakob; Kerschke, Pascal; Trautmann, Heike (Applied Sciences)
Due to the rise of continuous data-generating applications, analyzing data streams has gained increasing attention over the past decades. A core research area in stream data is stream classification, which categorizes or detects data points within an evolving stream of observations. Areas of stream classification are diverse— ranging, e.g., from monitoring sensor data to analyzing a wide range of (social) media applications. Research in stream classification is related to developing methods that adapt to the changing and potentially volatile data stream. It focuses on individual aspects of the stream classification pipeline, e.g., designing suitable algorithm architectures, an efficient train and test procedure, or detecting so-called concept drifts. As a result of the many different research questions and strands, the field is challenging to grasp, especially for beginners. This survey explores, summarizes, and categorizes work within the domain of stream classification and identifies core research threads over the past few years. It is structured based on the stream classification process to facilitate coordination within this complex topic, including common application scenarios and benchmarking data sets. Thus, both newcomers to the field and experts who want to widen their scope can gain (additional) insight into this research area and find starting points and pointers to more in-depth literature on specific issues and research directions in the field.
Keywords: big data; data mining; data stream analysis; machine learning; stream classification; supervised learning

On the Potential of Automated Algorithm Configuration on Multi-Modal Multi-Objective Optimization Problems - Rook, Jeroen; Trautmann, Heike; Bossek, Jakob; Grimme, Christian (Proceedings of the Genetic and Evolutionary Computation Conference Companion)
Hardness of Multi-Objective (MO) continuous optimization problems results from an interplay of various problem characteristics, e. g. the degree of multi-modality. We present a benchmark study of classical and diversity focused optimizers on multi-modal MO problems based on automated algorithm configuration. We show the large effect of the latter and investigate the trade-off between convergence in objective space and diversity in decision space.
Keywords: configuration; multi-modality; multi-objective optimization

Langhaarmädchen und Seinz. Geschlechterstereotype in Markennamen entdecken - Dübbert, Alexander; Kuhnau, Alexander (Praxis Deutsch)
Zahlreiche Marken verstärken durch den Einsatz von entsprechenden Namen sowie gestalterischen Zusätzen potenziell Geschlechterstereotype. Dieses Modell sensibilisiert dafür und regt zu einer Auseinandersetzung an.

Interkulturelle Gattungstransfers und - transformationen zwischen Europa und der Türkei am Beispiel des Schelmenromans - Schulte Eickholt, Swen; Perfölz, René (Jahrbuch für Interantionale Germanistik. Wege der Germanistik in transkultureller Perspektive. Akten des XIV. Kongresses der Interantionelen Vereinigung für Germanistik (IVG) (Bd. 11))

Losses Never Sleep - The Effect of Tax Loss Offset on Stock Market Returns during Economic Crises - Koch, Reinald; Holtmann, Svea; Giese, Henning

‘Authentic Englishes.nrw’ – Developing and Using Interactive Teaching and Learning Materials on Varieties of English - Pape, S.; Fiege, Amanda Sophie; Mindt, Ilka (Anglistik)
Keywords: General Medicine

Moodle in der Hochschullehre: Struktur durch HTML-Code - Fiege, Amanda Sophie; Pape, Stefan (#MoodleKannMehr – nicht nur im Distanzunterricht!)

Produktkennzeichnung durch lokal definierte Einstellung von ferromagnetischen Eigenschaften beim Drückwalzen von metastabilen Stahlwerkstoffen - Arian, Bahman; Homberg, Werner; Kersting, Lukas; Trächtler, Ansgar; Rozo Vasquez, Julian (36. Aachener Stahlkolloquium – Umformtechnik “Ideen Form geben“)

A flow forming process model to predict workpiece properties in AISI 304L - Arian, Bahman; Oesterwinter, Annika; Homberg, Werner; Rozo Vasquez, Julian; Walther, Frank; Kersting, Lukas; Trächtler, Ansgar (19th Int. Conference on Metal Forming 2022)

Lagerkapazitätsdimensionierung als betriebswirtschaftliches Entscheidungsproblem - Betz, Stefan (Aktuelle Fragestellungen zu Produktion, Controlling und Logistik)

Strategische Erfolgsplanung für Produktinnovationen - Betz, Stefan (Aktuelle Fragestellungen zu Produktion, Controlling und Logistik)

"Die Bombardierung von Brüssel - teil 2" (Podcast) - Huybrechts, Yves